High voltage optical sensor insulation using PLA (Polylactic Acid) - Barbosa, Kelvin Meira; Martinez, Guilherme Alves [UNESP]; Pereira, Fernando Da Cruz; Higuti, Ricardo Tokio [UNESP]; Kitano, Claudio [UNESP]; Galeti, Jose Henrique (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Electric power systems, especially after the advent of smart grids, require intelligent voltage and current meters devoted to energy billing, control, protection and quality monitoring. Novel Optical Voltage Sensors (OVS) schemes have been researched to address different electricity industrial applications. In this work, a case insulator bushing (CIB) was developed to pack an electro-optical crystal-based OVS, employing lithium niobate, for the voltage class of 13.8 kV and applied to protection and energy quality monitoring. The design and implementation of this CIB, provided with high isolation and the appropriate internal flexibility to meet the dimensional tolerances of the electro-optical sensor, was produced with Polylactic Acid (PLA) by using a 3D printer.
Keywords: 3D printing; Electrical insulation; Optical component packaging; Optical voltage sensor; PLA